ANALISIS KINERJA TENAGA SURVEILANS KESEHATAN (GASURKES) PROGRAM KESEHATAN IBU DAN ANAK DI KOTA SEMARANG - Prisma Armaya; Ayun Sriatmi; Septo Pawelas Arso (Jurnal Kesehatan Masyarakat (Undip), 2016)
In 2015 Semarang ranked second with cases of maternal deaths in Central Java with 35 cases in 2015. One of the efforts undertaken by the Health Department of Semarang in efforts to reduce maternal deaths in the city of Semarang was to recruit Tenaga Surveilans Kesehatan (Gasurkes) KIA. Gasurkes duty to perform data collection and assistance to pregnant women routinely until parturition. This study aims to analyze the performance of Gasurkes KIA seen on several variables such as knowledge and skills, resources, leadership, supervision, compensation, job design and structure, perception, and motivation. This research is a qualitative with in-depth interviews conducted in Gasurkes KIA, midwife coordinator, Semarang City Health Department, and for postpartum mothers. The results showed that the Gasurkes KIA overall performance is still not optimal seen from assisting pregnant women and postpartum mothers are not in accordance with the provisions Gasurkes. KIA still lack of skills in communication and coordination. There are problems in the system of monetary transport compensation to the Gasurkes KIA. midwife coordinator leadership is still lacking, leading to misunderstandings between midwife coordinator with Gasurkes KIA in its teritory. Motivation of Gasurkes KIA still limited from the support of family and co-workers, the lack of appreciation of the organization and working conditions are less favorable. To overcome these problems, the Semarang City Health Office should immediately implement training on communication techniques and good extension. Fixing the system of compensation money for transport by health centers, and improve coordination between the KIA Gasurkes Bikor. Make SOP to implement socialization Provide mentoring pregnant women about the existence Gasurkes KIA. Gasurkes KIA need to improve the quality of assistance so that pregnant women believe and would be accompanied Gasurkes KIA.